Vivências subjetivas de psicólogos(as) clínicos(as) no contexto do trabalho plataformizado - Bonfim, Jardel Melo (2024)
This research sought to investigate the process of clinical psychologists' experiences in relation to subordinate work through digital platforms. This is a qualitative study of an exploratory nature and for this purpose, a research collective was formed, with the voluntary participation of three psychologists from different regions of Brazil. The group took place online and lasted seven meetings. Clinical Work Analysis was used to organize and analyze the results, which was divided into three thematic axes: I - organization of the prescribed work and the actual work; II - experiences of pleasure and suffering; III - coping strategies. The findings showed that the organization and forms of control were not homogeneous. It was inferred that this diversification may contribute to the difficulty of recognizing the processes of precarious work in which clinical psychologists are involved. It was also identified that the organization of work is marked by algorithmic management and the neoliberal rationality of the business subject. Experiences of pleasure arise mainly from the social meaning of the work of being able to contribute to the process of change and evolution of their patients. In terms of experiences of suffering, the lack of transparency on the part of platforms regarding the storage and access to digital records was the main determinant, which causes ethical suffering, given that professional secrecy is one of the main characteristics of the work(a) psychologist. Coping strategies are predominantly individual defense, such as carrying out physical activity, not working on weekends, and denying or minimizing suffering as a psychic resource. However, a subjective mobilization was also identified, although incipient, marked mainly by the use of practical intelligence regarding the recording of medical records. As a contribution, the study brought findings that reinforce a critical position regarding the platformization of work, especially in the online psychological care service.